Cross-Categorial Formal Identity: A Functional Account - Luo, Cheng (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1991)
Linguistic change in morphology and syntax can involve inter-categorial transfer of the same form, often reflected synchronically through formal identity among coexisting categories. Such transfer can be motivated and conditioned by functional / semantic similarity between the categories involved. This study shows formal identity between the contrastive focus marker, the demonstrative and the copula in five languages: Mandarin, Hebrew, Margi, Mokilese and Kusaiean, where the three categories are shown to be by and large diachronically related. This relationship appears to be motivated by their sharing of the same functional domain of deixis.